STRESSING, PRONUNCIATION, AND SPEAKING EXERCISES IN “PATHWAY TO ENGLISH” TEXTBOOK - Harsya Danang Pradana (STKIP Persada Khatulistiwa Sintang, 2020)
Abstract: The aim of this research is to investigate how the “Pathway to English” textbook facilitates students’ learning of speaking, specifically in pronunciation and stressing of words. Learning the English language involves four skills: speaking, listening, reading, and writing. As such, textbooks need to be equipped to facilitate the teaching of these skills. However, globalization and the change in what types of English is accepted in broader world contexts may make the textbook obsolete. To see if the textbooks used in Indonesian High Schools are adequate enough to facilitate the teaching of stressing, pronunciation, and speaking, the researcher studied the “Pathway to English” textbook using a content analysis method to see if it has the necessary contents to facilitate the learning of stressing, pronunciation, and speaking. The results of this study shows that the textbook is inadequate to facilitate the learning of pronunciation and stressing, but it is equipped to facilitate the teaching of general English speaking skills. This means that English teachers in High Schools of Indonesia are expected to use supporting media to teach pronunciation and stressing when using the textbook.Keywords: Pathway to English; textbook; speaking; stressing; pronunciation